Vibrations of the low energy states of toluene ( X(1-A-1) and A(1-B-2) and the toluene cation (X+(2-B-1) - Gardner, Adrian M.; Green, Alistair M.; Tamé-Reyes, Victor M.; Wilton, Victoria H.K.; Wright, Timothy G. (American Institute of Physics, 2013)
We commence by presenting an overview of the assignment of the vibrational frequencies of the toluene molecule in its ground (S0) state. The assignment given is in terms of a recently-proposed nomenclature, which allows the ring-localized vibrations to be compared straightforwardly across different monosubstituted benzenes. The frequencies and assignments are based on a range of previous work, but also on calculated wavenumbers for both the fully hydrogenated (toluene-h8) and the deuterated-methyl group isotopologue (3-toluene-d3), obtained from density functional theory (DFT), including artifical-isotope shifts. For the S1 state, one-colour resonance-enhanced multiphoton ionization (REMPI) spectroscopy was employed, with the vibrational assignments also being based on previous work and time-dependent density functional theory (TDDFT) calculated values; but also making use of the activity observed in two-colour zero-kinetic-energy (ZEKE) spectroscopy. The ZEKE experiments were carried out employing a (1 + 1) ionization scheme, using various vibrational levels of the S1 state with an energy < 630 cm 1 as intermediates; as such we only discuss in detail the assignment of the REMPI spectra at wavenumbers < 700 cm 1, referring to the assignment of the ZEKE spectra concurrently. Comparison of the ZEKE spectra for the two toluene isotopologues, as well as with previously-reported dispersed-fluorescence spectra, and with the results of density functional theory (DFT) calculations, provide insight both into the assignment of the vibrations in the S1 and D0+ states, as well as the couplings between these vibrations. In particular, insight into the nature of a complicated Fermi resonance feature at ~ 460 cm 1 in the S1 state is obtained, and Fermi resonances in the cation are identified. Finally, we compare activity observed in both REMPI and ZEKE spectroscopy for both toluene isotopologues with that for fluorobenzene and chlorobenzene.